2017
DOI: 10.1515/hukin-2017-0015
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Serve Speed and Motor Coordination between Elite and Club Level Tennis Players

Abstract: The purpose of this study was to compare the serve speed and motor coordination of elite and club level junior tennis players aged 11-14 years. Participants (n=35) were assigned to one of the two groups according to their experience, weekly training volume and competition level. Serve speed was assessed with a sports radar gun. Motor coordination was evaluated by means of the Körperkoordinationstest für Kinder. The main results revealed that serve speed and motor coordination performance levels of the elite gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 21 publications
1
33
0
3
Order By: Relevance
“…Because of the paucity of investigations about the topic, it is difficult to compare our results with other studies. While the degree of motor coordination seems to be an important predictor of motor performance in different sports [12][13][14][15][16][17][18], little is known about this relationship in volleyball. Specifically in volleyball, Pion et al [19] found that high-level young female players had better motor coordination compared with their average-level peers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the paucity of investigations about the topic, it is difficult to compare our results with other studies. While the degree of motor coordination seems to be an important predictor of motor performance in different sports [12][13][14][15][16][17][18], little is known about this relationship in volleyball. Specifically in volleyball, Pion et al [19] found that high-level young female players had better motor coordination compared with their average-level peers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the relationship has also been investigated between the degree of motor coordination and performance in different sports [11], such as tennis [12,13], table tennis [14], soccer [15], gymnastic [16,17], judo [18], and volleyball [19]. Overall, these findings have suggested that the degree of motor coordination is an important predictor of sports performance in youth athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 shows the study authors; number, sex, age, performance level and tennis experience of subjects; measures of technical and tactical skills; and results reported in the 40 articles included in the review. Nine studies were included in the technical skills category (Girard, Micallef, & Millet, 2005, 2007Kolman, Huijgen, Kramer, Elferink-Gemser, & Visscher, 2017;Landlinger et al, 2012;Lyons, Al Nakeeb, Hankey, & Nevill, 2013;Martin, Bideau, Ropars, Delamarche, & Kulpa, 2014;Söğüt, 2017;Vergauwen et al, 2004;Vergauwen, Spaepen, Lefevre, & Hespel, 1998). Five of these studies were of high methodological quality and four were of good methodological quality.…”
Section: Methodsmentioning
confidence: 99%
“…Five of these studies were of high methodological quality and four were of good methodological quality. There was strong evidence that ball velocity produced in serves and/or groundstrokes differentiates professionals from advanced players and advanced players from intermediate players and novices (Girard et al, 2005(Girard et al, , 2007Kolman et al, 2017;Landlinger et al, 2012;Martin et al, 2014;Söğüt, 2017;Vergauwen et al, 1998Vergauwen et al, , 2004. The findings of Landlinger et al (2012) and Vergauwen et al (1998) showed higher ball velocities produced by forehand strokes compared with backhand strokes.…”
Section: Methodsmentioning
confidence: 99%
“…Coordination ability is a means of harmonizing individual elements of the movement in a single system for solving a specific motor task, which manifests itself in the accuracy and timeliness of its implementation (Bykova, 2016;Sogut, 2017).…”
Section: Introductionmentioning
confidence: 99%